Malachite Green Dye Adsorption from Aqueous Solution using a Ni/Al Layered Double Hydroxide-Graphene Oxide Composite Material - Amri Amri; Aldes Lesbani; Risfidian Mohadi (Science and Technology Indonesia, 2023)
Ni/Al layered double hydroxide and Ni/Al-graphene oxide composite materials were created using the coprecipitation method. The materials were successfully synthesized and prepared using XRD, FT-IR, and BET studies. The optimal pH as a result of malachite green dye adsorption is pH 4. The kinetics models of all materials follow the pseudo second order model. After being composited with graphene oxide, the maximum adsorption capacity of Ni/Al layered double hydroxide increased from 99.010 to 111.111 mg/g. All materials’ isotherm models adhere to the Langmuir isotherm model. The adsorption process was endothermic and spontaneous. The Ni/Al-graphene oxide composite material has a more stable structure than the Ni/Al layered double hydroxide. The regeneration procedure was repeated five times, and the Ni/Al-graphene oxide composite material did not show a significant decrease until thefifth cycle, when it dropped from 97.561 to 77.046%, however the Ni/Al layered double hydroxide material dropped rapidly from 85.00 to 5.667%.